Visual pollution and its impact on the population of the city of Kadhimiya (Journal of the College of Basic Education, 2023)
Summary of the research:The high degree of urbanization in the new modernization system has caused multiple problems within the city environment, including visual pollution, which greatly affected the city’s residents through unattractive scenes that led to distortion of the city’s landscape, while these scenes cause discomfort, discomfort and anxiety to humans in the long run so that He loses sense and beauty around him, and transforms the environment in which a person lives into a place full of negative elements that led to the concealment of aesthetic images from everything, and the emergence of psychological and physical diseases that affect a person’s daily life. The research included an introduction and the theoretical framework with two sections, as the first topic included the forms of visual pollution, its sources and its measurement. As for the second topic, the psychological damage resulting from visual pollution, the research concluded with a set of results and proposals.